Validity of Electrolyte and Non Electrolyte Solution Modules Basedon Guided Inquiryto Train High Level Thinking for Class Students X SMA/MA - Suci Sri Maidani; Iryani Iryani (Universitas Negeri Padang, 2022)
Electrolyte and non electrolyte solution material is an abstract material that requires multiple representations in the learning process to accordance with the demands of the 2013 curriculum for studying material at the SMA/MA level. Learning will be optimal if it is supported by teaching materials in the form of modules. This study aims to produce a guided inquiry based electrolyte and non electrolyte solution module to train higher otder thinking and determine the level of validity of the resulting product. The type of research used isEducational Design Research with the Plomp development model. The reearch instrument used was a validity questionnaire which was processed using the Aiken’s V formula. Keywords:Module, Electrolyte and Non Electrolyte Solution, Guided Inquiry, Higher Order Thinking, Plomp Model Materi larutan elektrolit dan non elektrolit adalah materi yang bersifat abstrak sehingga membutuhkan multiple representasi dalam proses pembelajaran sesuai dengan tuntutan kurikulum 2013 dalam mempelajari materi pada tingkat SMA/MA. Pembelajaran tersebut akan optimal jika ditunjang dengan sebuah bahan ajar seperti modul. Penelitian ini bertujuan untuk menghasilkan modul larutan elektrolit dan non elektrolit berbasis inkuiri terbimbing untuk melatih berpikir tingkat tinggi dan menentukan tingkat validitas modul tersebut. Jenis penelitian yang dipakai ialah Educational Design Research dengan model pengembangan Plomp. Instrumen penelitian yang digunakan adalah angket validitas yang diolah menggunakan rumus Aiken’s V. Kata Kunci: Modul, Larutan elektrolit dan Non elektrolit, Inkuiri Terbimbing, Berpikir Tingkat Tinggi, Model Plomp